Economics of Production of Tomato under Open and Protected Field Condition in Hills of Uttarakhand - Jethi, Renu; Srinivas, K; Bisht, J.K (Indian Journal of Extension Education, 2023)
In present study, an attempt is made to work out the economics of production of tomato under open and protected field  condition in Almora and Nainital districts of Uttarakhand. The study is based on primary data of seventy six farmers  engaged in vegetable cultivation. Simple tabular analysis and standard cost concept was used to work out the cost of  cultivation. The study revealed that the total cost of cultivation of tomato under open and protected field condition was` 1,36,250 and ` 4,01,743 per hectare and gross return was ` 1,81,500 and ` 8,66,250 per hectare respectively. The output input relationship for tomato was 1.3 and 2.2 at cost 'C' under open and protected field conditions was respectively. In  order to find suitability of poly-houses for cultivation of tomato, economic indicators such as net present value, benefit  cost ratio and pay back period were also calculated.
Keywords: Tomato production; Net present value; Internal rate of return; Benefit cost ratio; Return over investment